Physical characteristics and reproductive performance in Aedes (Diptera: Culicidae) - Hamady, Dieng; Fatimah, Abang; Ahmad, Abu Hassan; Gabriel Tonga, Noweg (PAGEPress, 2016)
Body size is a physical factor of crucial importance underlying important traits of the reproductive dynamics of both sexes in mosquitoes. Most studies on the influence of body size in mating success of dengue vectors addressed sperm transfer to females and did not consider egg production, a prerequisite for population maintenance; male body size impact on reproduction has attracted little research interest with respect to sterile insect technique. In experiments involving differently sized adults, we examined whether the body size of the mates is a source of variation in reproductive outcome in Aedes aegypti. In the absence of male partners, large females (LF) showed better fecundity than small females (SF). In intraclass mating trials, egg production was much greater in largesized than smallsized pairs. There were comparable fecundities in large females mated with small males and large pairs. [SF•SM] and [SF•LM] pairs showed equivalent fecundity. Nonmating did not result in the production of viable eggs by either small or large females. We also observed that eggs produced by largesized females mated with small males had better hatching success than those from either small or large pairs. Mating between small females and large males resulted in poor egg viability.